Urgensi Perlindungan Hukum Perusahaan Exchanger Cryptocurrency Terhadap Aliran Transaksi dari Pengguna Anonim Wallet Decentralize Exchange - Basit Barry (Publikasi Indonesia, 2023)
In its development, the use of crypto assets as an option for investing has shifted to be used as a new mode of money laundering. Cryptocurrency Exchange Companies have a strategic role in terms of preventing the occurrence of criminal acts of money laundering through crypto assets, this is because cryptocurrency exchange companies as an entry point and as an initial screening for the occurrence of buying and/or buying crypto assets carried out by actors. Cryptocurrency Exchange Companies are required to be reporting parties to Suspicious Financial Transactions (TKM) in TPPU. Data analysis in this study uses qualitative descriptive analysis methods with legal, statutory, and conceptual protection approaches. The results of this study state that the Need for Legal Protection for Cryptocurrency Exchange Companies as the receiving party to the flow of transactions from anonymous users (consisting of only one line of wallet addresses with a unique combination of letters and numbers) Wallet Decentralize Exchange (Dex) is necessary for a good faith Cryptocurrency Exchange Company to report every existing transaction, even though the reporting format cannot include an identity Service users, get guaranteed legal protection so as not to be subject to sanctions, both administrative sanctions and criminal sanctions. The form of legal protection that can be given to cryptocurrency exchange companies as reporting parties, is divided into 3 (three), namely Protection due to the guarantee of the Law in the form of Release from civil and criminal claims, Protection Due to the Implementation of the TPPU Law in the form of keeping the identity of the reporting party confidential, Special Protection by the National Police of the Republic of Indonesia in the form of personal security from physical and mental threats, to property, disguise of identity and Giving information without face to face (confrontation) with the suspect or defendant.